2006
DOI: 10.1080/00498250600790331
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of paraquat in the isolated rat lung: Influence of sodium depletion

Abstract: Paraquat accumulates in the lung through a characteristic polyamine uptake system. It has been previously shown that paraquat uptake can be significantly prevented if extracellular sodium (Na+) is reduced, although the available data correspond to experiments performed using tissue slices or incubated cells. This type of in vitro study fails to give information on the actual behaviour occurring in vivo since the anatomy and physiology of the studied tissue is disrupted. Accordingly, the aim of the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Paraquat accumulates in the lung through a characteristic polyamine uptake system. Several studies have been undertaken with regard to paraquat as a useful tool for the exploration of the early pathogenesis of pulmonary injury (20).…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat accumulates in the lung through a characteristic polyamine uptake system. Several studies have been undertaken with regard to paraquat as a useful tool for the exploration of the early pathogenesis of pulmonary injury (20).…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively demonstrated that it is highly toxic to multiorgans when absorbed through ingestion, skin contact, or inhalation. The primary target organ for PQ toxicity is the lung as a consequence of its accumulation, against a concentration gradient, through the highly developed polyamine uptake system [1–3]. The toxicity mechanism of PQ is mainly due to a sustained redox-cycling effect, resulting in oxidative stress-related insults such as lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The lung is considered the primary target organ for PQ toxicity as a consequence of the accumulation of PQ against a concentration gradient via the highly developed polyamine-uptake system (Dinis-Oliveira et al, 2006a, 2006bChang et al, 2009). The primary effect of PQ toxicity is seen in the lungs, where PQ gets accumulated via a process of active transport in the Clara cells and alveolar type I and type II epithelial cells, leading initially to pulmonary edema, infiltration of inflammatory cells, and damage to the alveolar epithelium, and later progressing to lung fibrosis and respiratory failure (Smith and Heath, 1975;Thurlbeck and Thurlbeck, 1976;Tomita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%